Efforts To Improve Cognitive Ability To Know Color Using Pompom Media In Early Children - Ubaidillah Ubaidillah; Wahyu Erfaliana; Wulan Dwi Cahyani; Nur Hayati; Nasikhatul Azimah (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
Cognitive development is often identified with the development of intelligence. Cognitive development is the basis for the development of intelligence in children. In early childhood, knowledge is still subjective, and will develop into objective when it reaches adolescent and adult development. This is where it is important for teachers and parents to supervise children's lives in the surrounding environment. Based on the results of the findings obtained through activities to improve cognitive abilities to recognize colors using Pompom media, 2 (two) cycles were carried out through observing the ability to recognize colors and grouping colors using Pompom media. In the observation activity, the ability to recognize colors and group colors using pompom media starting from cycle I, cycle II shows that the students' ability to recognize colors and group colors using Pompom media is very good, this is in accordance with the percentage of observation results recognizing colors and grouping colors using Pompom media in cycle I namely the highest percentage from 75%, to 100% in cycle II. The overall average was from 48.4% in cycle I to 75.8% in cycle II.